Quality standards and academic evaluation of scientific research in universities - Al-Sawy, Yasser Mohammed Mohammed (Qualitative and Quantitative Methods in Libraries; Vol 8 No 1 (2019): March 2019 Issue, 2019)
The excellence in standards and determinants of total quality and accreditation in scientific research is one of the most important standards of academic evaluation in according to the internationally accredited standards in universities, which are based on well-established scientific foundations at the global level. Fulfilling these standards helps to achieve the desired development goals. Through the application of descriptive and analytical approach, The present research aims at the realization of the dimensions of several research axes that ensure the quality standards of scientific research within the system of academic evaluation of the university, including: the promotion of scientific research excellence in the university institutions, the interest in quality output of the Scientific research in accordance with the standards of ‘Web of Science’, the encouragement for publication in internationally reliable magazines and journals, which is controlled scientifically through accredited academic and research entities, the promotion of the scientific publication that is adopted for innovative research, as well as the improvement of the scientific arbitration quality to keep up with the technological advent in the management of scientific research.